ANALISIS PENGARUH STRUKTUR ORGANISASI TERHADAP KOMITMEN KEORGANISASIAN DENGAN MEDIASI PENGAMBILAN KEPUTUSAN PADA ANGGOTA KORPS BRIMOB POLRI - Ardi Kurniawan; Pantius Drahen Soeling (Jurnal Akuntansi dan Pajak, 2023)
The focus of this research is to examine the relationship between organizational structure and organizational commitment with decision making as a mediator. This study uses a quantitative approach, namely examining the population or sample, collecting data using research instruments, analyzing data statistically with the aim of testing the specified hypothesis. Primary data collection by distributing questionnaires to 260 respondents. Data analysis used SPSS software, which was run on PLS (Partial Least Square) computer media, which is a variant-based structural equation analysis that can simultaneously test measurement models as well as test structural models. Based on the research results, it can be concluded that organizational structure variables affect organizational commitment. If the direct influence relationship between organizational structure and organizational commitment does not have a significant effect, but if these variables are mediated by decision making, then the results state that there is a significant positive influence relationship between the two variables. This shows that decision making has a significant role in mediating the relationship between organizational structure and organizational commitment.